First multicentre experience of SABR for lymph node and liver oligometastatic disease on the unity MR-Linac - On Behalf of the tumor site group for oligometastatic disease of the Elekta MR-Linac Consortium (Elsevier Ireland Ltd, 2022)
The treatment of oligometastatic disease using MR guidance is an evolving field. Since August 2018 patients are treated on a 1.5 Tesla MR-Linac (MRL). We present current workflows and practice standards from seven institutions for the initial patients treated for lymph node and liver metastases.
Keywords: (3–6): oligometastases; MOMENTUM; MR-guided radiotherapy; MR-Linac; SABR; Care Planning; Oncology(nursing); Health Policy; Radiology Nuclear Medicine and imaging; Journal Article